Модель системи підготовки майбутніх фахівців з фізичного виховання i спорту до реабілітаційної роботи з дітьми з обмеженими фізичними можливостями - Долинний, Юрій (My University, 2017)
Моделювання в педагогіці, порівняно з багатьма іншими галузями людського знання, має особливості, природа яких ґрунтується на нечіткості, розпливчастості педагогічних понять. Модель системи підготовки майбутніх фахівців з фізичного виховання i спорту до реабілітаційної роботи з дітьми з обмеженими фізичними можливостями є найважливішим завданням підготовки фахівців з «фізичної терапії, ерготерапії». Представлена модель передбачає : уточнення смислу понять «модель» у педагогічному аспекті; визначення теоретико-методологічних основ моделювання процесу підготовки майбутніх фахівців з фізичного виховання i спорту до реабілітаційної роботи; формулювання методологічних принципів побудови моделі; розробки й опису моделі підготовки майбутніх фахівців з фізичного виховання i спорту до реабілітаційної роботи. Модель системи підготовки майбутніх фахівців з фізичного виховання i спорту до реабілітаційної роботи з дітьми з обмеженими фізичними можливостями складається з теоретично - цільового, структурно - змістового, діагностично-результативного напрямку підготовки. Результатом впровадження представленої моделі є професійна компетентність майбутнього фахівця з фізичного виховання і спорту що до фізичної терапії, ерготерапії, фізичної реабілітації дітей з обмеженими фізичними можливостями. Vital experience, practice of physical education and sport, specify on that process of rehabilitation of people with the limited physical possibilities, must begin as possibly before in child's age. Therefore the issue of the day of modern pedagogical theory and practice is a process of creation of model of professional preparation of future specialists on physical education and sport to rehabilitation work with children with the limited physical possibilities at higher school. A design in pedagogics, by comparison to many other industries of human knowledge, has features, nature of which is based on an unclearness, diffusion of pedagogical concepts. Model of the system of preparation of future specialists on physical education and sport to rehabilitation work with children with the limited physical possibilities is the major task of preparation of specialists on «physical therapy, ergoterapii». The presented model provides for: clarification of sense of concepts «model» is in a pedagogical aspect; determination of theoretic-methodological bases of design of process of preparation of future specialists to on physical education and sport to rehabilitation work; formulation of methodological principles of construction of model; developments and descriptions of model of preparation of future specialists on physical education and sport to rehabilitation work. Model of the system of preparation of future specialists on physical education and sport to rehabilitation work with children with the limited physical possibilities of folded from in theory-having a special purpose, structurally-semantic, diagnostically-effective direction of preparation. The result of introduction of the presented model is a professional competence of future specialist on physical education and sport that to physical therapy, ergoterapii, to the physical rehabilitation of children with the limited physical possibilities. Becoming our state, democratic development of society, social policy of Ukraine, requires passing to the new type humanism innovative athletic education, which is carried out on the basis of introduction of new maintenance, forms, methods of studies, upgrading professional preparation of future specialists, on physical education and sport, to rehabilitation work with children with the limited physical possibilities.
Keywords: модель; підготовка; фахівці; фізичне виховання; реабілітаційна робота; обмежені фізичні можливості